The Relationship between Geography and Economic History in the Formation of Indonesian Development Policy - Fadillah, Nurul; Dalimunthe, Mahdini; Daulay, Rahmadhani Fadhlina; Putri, Lia Anita; Yusnaldi, Eka (JUPE : Jurnal Pendidikan Mandala, 2024)
Geography is a science that is more focused on the interaction between humans and the environment in which they live (Hobbs, 2009). Geography places more emphasis on interactions between humans and their environment. Humans live on the surface of the earth where each area or region on the surface of the earth certainly has characteristics that differentiate one place from another. Economic geography is a subfield of human geography that studies the relationship between economic and geographical factors. This research uses qualitative methods, namely data collection methods through observation, visual analysis, literature study, and interviews (both individual and group). According to Sugiyono, qualitative research methods are based on the philosophy used to research scientific conditions (experiments) where the researcher acts as the main instrument, with qualitative data collection techniques and data analysis that places greater emphasis on meaning. The results of this research are that the relationship between economic geography aims to increase or improve human income or economy in a better or more prosperous direction, both the Indonesian economy before independence until the New Order era.